Geochemical constraints on the evolution of the Proterozoic continental crust in southern Norway (Telemark sector). - Smalley,PC; Field,D (1985)
The Proterozoic continental crust of the Telemark sector consists of supracrustal gneisses and several later plutonic suites intruded between 1.6 and 1.25 Ga ago. The chemical evolution is similar to that observed in modern cordilleran orogens, in the transition from island and primitive continental arcs to mature continental and back arc-anorogenic environments, and is interpreted in terms of variation in sub-crustal source composition. The earliest rocks were derived from previously depleted mantle which had experienced subduction-related enrichment in LILE via hydrous fluids originating in the subducted slab at the time of, or shortly before, magma generation. The later rocks have an increasing component derived from a within-plate mantle type, which had been modified by the introduction of non-subduction-related CO2 - rich LILE- and HFSE- bearing fluids or partial melts. These geochemical signatures developed during accretion of the Proterozoic south Norwegian crust above a W-migrating, E-dipping subduction zone. -from Authors